Development of disclosure and transparency as legal methods for the supervision of public companies in the Republic of Slovenia - Djokić, Danila (Management, 2012)
As a rule, public companies in the Republic of Slovenia use a twotier system of corporate governance. The supervisory boards of such companies should execute the supervisory function by informing and disclosing to the shareholders the data regarding envisaged policies of corporate governance. The principle of disclosure and transparency in general, and in the field of remuneration, is used in the Republic of Slovenia as a systemic legal method and tool, which enables better decision making processes, supervision and control of public companies in the country.
Keywords: javna podjetja; korporacije; management; nadzor; pravna ureditev; Slovenia; Slovenija; upravljanje; varstvo podatkov; vodenje